Sodium: The forgotten nutrient - Bergeron, M. F. (2000)
* Athletes lose far more sodium and chloride in sweat than any other electrolytes. * Sodium and chloride losses are greater with higher sweating rates. * Sodium and chloride losses in sweat are usually less when an athlete is acclimatized to the heat. * To completely replace body fluids after exercise, an athlete must replace the sodium and chloride that were lost through sweating. * Sodium deficits can lead to incomplete rehydration and muscle cramps. * Excessive rapid water consumption, combined with a large sweat-induced sodium deficit, can lead to hyponatremia, a potentially deadly reduction in blood levels of sodium.